The interface : IBM and the transformation of corporate design, 1945/1976 - Harwood, John, 1977- (Quadrant Book., 2011)
In February 1956 the president of IBM, Thomas Watson Jr., hired the industrial designer and architect Eliot F. Noyes, charging him with reinventing IBM's corporate image, from stationery and curtains to products such as typewriters and computers and to laboratory and administration buildings. What followed-a story told in full for the first time in John Harwood's The Interface-remade IBM in a way that would also transform the relationships between design, computer science, and corporate culture. IBM's program assembled a cast of leading figures in American design: Noyes, Charles Eames, Paul Ra.